PROSTHETIC REHABILITATION USING IMPLANTS AFTER ENUCLEATION OF AN EXTENSIVE MANDIBULAR MULTILOCULAR DENTIGEROUS CYST: A CASE REPORT - Dorelia Lucia Călin; Anca Rusu; Mihaela Mitrea (Romanian Society of Oral Rehabilitation, 2015)
Dentigerous cysts are the most common odontogenic developmental cyst being associated to an impacted tooth. They are usually asymptomatic and are discovered on routine radiographic examinations performed in order to identify the absence of tooth on the arch. The purpose of this case report is to present the spontaneous recovery of a bone defect without the need for bone addition material, as a result of enucleation of large mandibular multilocular dentigerous cyst together with the impacted tooth and the subsequent prosthetic rehabilitation of partial edentulism with dental implants. After 6 months after cystectomy, at the radiographic examination (OPG and CT) was noted the disappearance of almost all of the radiolucency and the formation of a sufficient quantity of bone for the insertion of the implants.They had good primary stability. By loading the implants and the fixed partial denture, functional, physiognomic and psychological needs of the patient have been fulfilled successfully, not being detected the cyst recurrence. Prosthetic rehabilitation with dental implants was the best solution in order to replace the missing teeth in case of an adequate bone regeneration.